Reconfiguring the breastfeeding body in urban public spaces - Mathews, Vanessa (Social & cultural geography, 2019)
The breastfeeding body is subject to overt and subversive forms of regulation and control in contemporary society, where it is sexualized and naturalized, rendered both visible and invisible, revered and found disruptive. Despite health policy espousing the benefits of breastfeeding for mother and child, duration rates in Canada remain relatively low. In this paper, I explore the spatial practices of the breastfeeding body in public, using feminist work on the body and theorizations of built form, urban space and embodied practice. Drawing on a series of feminist autoethnographic vignettes, I write my breastfeeding body into a diversity of routine urban spaces - a car, grocery store, mall, bookstore, highway, alleyway - and narrate my experiences negotiating social responses and spatial arrangements. I argue that the breastfeeding body challenges normative understandings of gender, motherhood and sexuality through its participation and presence in public space. The breastfeeding body transgresses the meaning of space and the performance of identity as it claims space for private use.